Assessment of ultrasonic root surface scaling with different power settings. roughness evaluation. - Renato Corrêa Viana Casarin; Fernando Rodrigues Pinto; Francisco Humberto Nociti Júnior; Enilson Antônio Sallum; Antônio Wilson Sallum; Márcio Zaffalon Casati (Universidade Estadual de Campinas, 2015)
Ultrasonic and curette instrumentation produces a rougher root surface which could be influenced by working parameters such as instrumentation time, pressure and tip angulations. Thus, the aim of this in vitro study was to evaluate root roughness after ultrasonic instrumentation with different power settings and compared it to curette instrumentation. Ninety extracted human teeth were assigned to one of five groups: control group (without instrumentation), curette instrumentation, ultrasonic instrumentation with low, medium, and high power. Before and after instrumentation, surface roughness was measured with a profilometer and the surfaces were examined under the SEM. The mean roughness values of the treated roots were higher than the non-treated roots (0.40+0.08mm). Roots treated by ultrasonic instrumentation had higher roughness means than roots treated by curettes (1.120+0.241mm). Among ultrasonic groups, the higher power setting produced the higher roughness mean (1.58+0.23mm), which was significantly higher than the roughness obtained with the low power setting (1.39+0.18mm). These findings show that ultrasonic instrumentation with a high power setting produced a rougher root surface than ultrasonic instrumentation with a lower power setting. In addition, manual instrumentation with curettes produced lower roughness than ultrasonic instrumentation independent of power setting